Comparative life cycle analysis of façade passive systems in the Mediterranean: Comfort, energy, and carbon. (April 2020) - Mifsud, Lara; Pomponi, Francesco; Moncaster, Alice M.
Abstract: In the Mediterranean region façade shading systems are used to reduce operational energy, particularly cooling loads. However, operational savings do not necessarily translate into net energy savings unless they outweigh the embodied energy/carbon required to manufacture, install, maintain, and dispose of these systems. This study analyses two shading devices, louvers and meshes, from a whole-life perspective in Malta. We first establish, through dynamic energy modelling, the operational energy and carbon savings achieved, and results show that both louvers and meshes are capable of savings in terms of operational energy—20%–40% compared to the base case. Secondly, we establish the embodied energy and carbon through a life cycle analysis. Although based on the limited data available for Malta, findings suggest that net energy and carbon savings are only achieved by two of the 22 configurations investigated, both mesh systems. These results highlight the urgent need to investigate shading systems to establish net energy and carbon whole-life balances. The risk is otherwise that we will save less operational energy in the future, from decarbonised energy grids, than we have already spent through a surge of embodied energy from current, carbon intensive grids, therefore exacerbating the climate crisis. Highlights: Horizontal louvers and vertical meshes are analysed as façade passive design strategies in Malta. In addition to comfort, life cycle energy and carbon have also been studied. Operational energy savings only rarely translate into net energy savings from a whole life perspective. Only two out of 22 configurations investigated yield net beneficial effect on both energy and carbon. Energy saving interventions should always be analysed from a life cycle perspective.